Peroxidase evolution in white-rot fungi follows wood lignin evolution in plants - Ayuso-Fernández, Iván; Rencoret, Jorge; Gutiérrez, Ana; Ruiz-Dueñas, Francisco Javier; Martínez, Angel T. (Proceedings of the National Academy of Sciences - PNAS, 2019)
A comparison of sequenced Agaricomycotina genomes suggests that efficient degradation of wood lignin was associated with the appearance of secreted peroxidases with a solvent-exposed catalytic tryptophan. This hypothesis is experimentally demonstrated here by resurrecting ancestral fungal peroxidases, after sequence reconstruction from genomes of extant white-rot Polyporales, and evaluating their oxidative attack on the lignin polymer by state-of-the-art analytical techniques. Rapid stopped-flow estimation of the transient-state constants for the 2 successive one-electron transfers from lignin to the peroxide-activated enzyme (k2app and k3app ) showed a progressive increase during peroxidase evolution (up to 50-fold higher values for the rate-limiting k3app ). The above agreed with 2-dimensional NMR analyses during steady-state treatments of hardwood lignin, showing that its degradation (estimated from the normalized aromatic signals of lignin units compared with a control) and syringyl-to-guaiacyl ratio increased with the enzyme evolutionary distance from the first peroxidase ancestor. More interestingly, the stopped-flow estimations of electron transfer rates also showed how the most recent peroxidase ancestors that already incorporated the exposed tryptophan into their molecular structure (as well as the extant lignin peroxidase) were comparatively more efficient at oxidizing hardwood (angiosperm) lignin, while the most ancestral “tryptophanless” enzymes were more efficient at abstracting electrons from softwood (conifer) lignin. A time calibration of the ancestry of Polyporales peroxidases localized the appearance of the first peroxidase with a solvent-exposed catalytic tryptophan to 194 ± 70 Mya, coincident with the diversification of angiosperm plants characterized by the appearance of dimethoxylated syringyl lignin units.